Exploring the Use of Kahoot a Game-Based Learning Tools in Vocabulary to Senior High School Students: A Systematic Review - Maemanah, Ana; Shofiana , Khelin Layla (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
This study examines the effectiveness of Kahoot as a game-based learning tool for vocabulary instruction among senior high school students. By conducting a systematic review of 16 empirical studies published between 2019 and 2025, this study identifies how Kahoot improves vocabulary learning outcomes. Findings show that Kahoot significantly improves vocabulary achievement by increasing student engagement, motivation and retention. Key features such as visual-audio interactivity, real-time feedback and competitive elements contribute to its effectiveness. Students expressed a strong preference for Kahoot over traditional methods due to its fun and interactive nature. Although short-term benefits were prominent, this review suggests the need for further studies on long-term vocabulary retention and comparative effectiveness with other platforms. The results of this study provide practical recommendations for teachers to meaningfully integrate Kahoot in vocabulary teaching and highlight its potential as a support tool in the EFL classroom.